Synthesis and Low Temperature Crystal Structure of Disodium Tetrapotasium Decavanadate - M. R. Mohammadi; M. Hakimi (E-Journal of Chemistry)
A decavanadate K4Na2V10O28.10H2O has been prepared and chractrisized by, IR and Raman spectroscopy. Single crystal x-ray analysis has been carried out on H20K4Na2O38V10 which crystallizes in the triclinic. System, space group P-1, with a=8.5584(5) Å, b=10.3041(6), c=10.9801(7) and Z=1. Structural units (V10O286-) link by the interstitial contents ([K4Na2(H2O)20]6+).